Vinorelbine and Docetaxel Combination as the First Line Treatment in Patients with Metastatic Breast Cancer: Results of a Multi-centric Phase II Trial in Iran - Moghadam, Shiva; Ameri, Ahamad; Shahrad, Behrouz; Fazlalizadeh, Abollah; Madani, Hossein; Mousavizadeh, Ahmad (Reports of Radiotherapy and Oncology, 2024)
Introduction: We conducted a multi-centric phase II study to evaluate the tumor response and safety of the combination of vinorelbin and docetaxel in treatment of metastatic breast cancer patients. Patients and Methods: Forty one metastatic breast cancer patients, who had at least one measurable lesion and had not been treated for metastasis before, were enrolled from March 2006 to June 2009. Treatment contained vinorelbine 25mg/m2 [Click and drag to move] [Click and drag to move] IV and docetaxel 30mg/m2 [Click and drag to move] [Click and drag to move] at day 1 and 8. Cycles were repeated every 21 days for 6 cycles. We evaluated response to chemotherapy every three weeks and toxicity every week. Results: The mean age of patients was 50.4 years (range 30-81). Twenty eight patients (68.2%) had received prior neoadjuvant anthracycline based chemotherapy. No patient had received adjuvant chemotherapy within the last 3 months. Twenty four patients (58.3%) had two or more metastatic sites. Thirty six patients were evaluable for their response. An objective tumor response (either complete response or partial response) was achieved in 32 (88.8%) and complete response was seen in 9 (25%) patients. Thirteen patients (31.6%) developed grade 3-4 neutropenia and neutropenic fever was reported in 11 (26.8%). Grade 3 anemia was observed in 1 patient (2.4%). No grade 4 non-hematological toxicity was noted and the most frequent grade 3 non-hematological toxicities were hair loss (39%), stomatitis (7.3%) and diarrhea (4.8%). Median time to progression was 7 months and median overall survival was 11 months. Conclusion: Vinorelbine-docetaxel combination shows a considerable tumor response and manageable toxicity as the first line treatment for metastatic breast cancer. It seems logical to conduct phase III trials to further evaluate this regimen.